Effects of hydrogenation on the tensile and shear mechanical properties of defective penta-graphene. (15th September 2021) - Han, Tongwei; Dong, Jabin; Wang, Xueyi; Zhang, Xiaoyan; Lv, Yikai; Scarpa, Fabrizio
Abstract: Penta-graphene (PG) is a new theoretical two-dimensional metastable carbon allotrope composed entirely of carbon pentagons. In this paper, molecular dynamics simulations are performed to investigate the effects of the hydrogenation on the tensile and shear mechanical properties, together with the failure mechanism of PG with vacancy defects. The results show that hydrogenation can effectively tune the mechanical properties and failure mechanism of PG with vacancy defects. The defective PG (DPG) with low hydrogenation coverages exhibits obvious plastic deformation features under tensile and shear loading, and pentagon-to-polygon structural transformation is observed, while complete hydrogenation can change the failure mechanism of DPG from plastic deformation to brittle fracture. Both the tensile and shear moduli and elastic limit of DPG first decrease dramatically and then increase slowly with the increase of hydrogenation coverage, while tensile and shear strain increases almost monotonically with rising hydrogenation coverage. Complete hydrogenation can result in large enhancement of tensile and shear elastic stress limit and strain. These results may provide an important guideline for effectively tuning the mechanical properties of PG and other two-dimensional nanomaterials.